Oral Health Literacy among School Students in Jodhpur City, Rajasthan, India - Anahita Ali (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: In India, only 25% community health centers have dentists available, but these infrastructures do not carry adequate instruments and other dental materials. This study aimed to examine the level of oral health knowledge, attitudes and practice behaviors among school students.Subjects and Method: This was a cross-sectional study conducted in Jodhpur City, Rajasthan, India. A total of 684 students of grade 9th & 10th from a private school were selected for this study. The data were collected by semi-structured questionnaire. The data were analyzed using a logistic regression.Results: 297 (43.42%) participants reported wrong number (32 teeth) of teeth during teenage. 620 (90.64%) participants answered ‘Yes’ that sweet food items, soft drinks and chewing gums are responsible for tooth decay. 377 (55%) students agreed that fluoridated toothpaste helps in prevention of tooth decay. The correct technique of tooth brushing reported by 325 (48%) participants is circular direction and up-down vertical direction by 223 (33%) of them. 621 (90%) said that ‘bleeding gums is the primary sign of bad oral health’. Dentist is the major source of information of 462 (68%) participants. 58 (8.5%) of them used other cleaning aids such as tongue cleaners, chewing gums, 120 (17.5%) did not use any cleaning aid. The regression analysis showed significant association between gender and regular dental visits (p=0.021), once and twice brushing habits daily, (p=0.015, p= 0.020) respectively.Conclusion: Oral health literacy levels among students were good to fair.Keywords: oral health behavior, health promotion, oral health literacyCorrespondence: Dr. Anahita Ali. Jodhpur School of Public Health, Maulana Azad University, Kamla Nehru Nagar, Jodhpur, Rajasthan, India- 342008. Email: anahitaali1@gmail.com Mobile: +917023830675.Journal of Health Promotion and Behavior (2020): 114-123https://doi.org/10.26911/thejhpb.2020.05.02.06